Sao Tome and Principe : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper highlights that the financial performance of Sao Tome and Principe, after improving in 1995, deteriorated again in 1996, while production continued to stagnate. In 1995, the authorities adopted policies aimed at stabilizing the economy, which led to a significant improvement in the fiscal position. The strengthening of control over monetary expansion made possible a reduction of end-of-period inflation to 37 percent, from 75 percent in 1994. In 1996, however, fiscal slippages and the consequent monetary financing of the budget deficits resulted in a resurgence of inflation and currency depreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet